2004
DOI: 10.1001/archpedi.158.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pulse Oximetry and Oxygen Therapy on Length of Stay in Bronchiolitis Hospitalizations

Abstract: Hospitalizations of some infants with bronchiolitis are prolonged by a perceived need for supplemental oxygen therapy based on pulse oximetry readings. Further investigation into outcomes of different levels and durations of oxygen desaturation is needed and would have the potential to reduce practice variability and shorten the length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 15 publications
3
114
0
3
Order By: Relevance
“…1 Continuous pulse oximetry (CPOx) monitoring of children hospitalized with acute respiratory disease may provide important data for titrating supplemental oxygen, but once the child's status has improved, CPOx adds little value and may prolong hospital stays. 2 Existing evidence suggests pulse oximetry readings may contribute to higher admission rates 1 and an increase in average length of stay (LOS) in bronchiolitis. 2 In its bronchiolitis guidelines, the American Academy of Pediatrics emphasized the uncertain role for CPOx in the inpatient setting, citing risk of prolonged hospital stay resulting from "perceived need for supplemental oxygen."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Continuous pulse oximetry (CPOx) monitoring of children hospitalized with acute respiratory disease may provide important data for titrating supplemental oxygen, but once the child's status has improved, CPOx adds little value and may prolong hospital stays. 2 Existing evidence suggests pulse oximetry readings may contribute to higher admission rates 1 and an increase in average length of stay (LOS) in bronchiolitis. 2 In its bronchiolitis guidelines, the American Academy of Pediatrics emphasized the uncertain role for CPOx in the inpatient setting, citing risk of prolonged hospital stay resulting from "perceived need for supplemental oxygen."…”
Section: Discussionmentioning
confidence: 99%
“…2 Existing evidence suggests pulse oximetry readings may contribute to higher admission rates 1 and an increase in average length of stay (LOS) in bronchiolitis. 2 In its bronchiolitis guidelines, the American Academy of Pediatrics emphasized the uncertain role for CPOx in the inpatient setting, citing risk of prolonged hospital stay resulting from "perceived need for supplemental oxygen." 3 Studies in adults have also highlighted the contribution of CPOx to alarm counts on units, [4][5][6][7][8] which the Joint Commission has emphasized as a patient safety issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Hypoxia complicates 70% to 84% of bronchiolitis admissions, prolonging hospital stay by 1.6 days and representing the leading barrier to discharge. [5][6][7] Small changes in oxygen level have a significant impact on decisions to admit, suggesting that pulse oximetry could drive increased admissions in the face of stable mortality rates. [8][9][10] Pediatric hospitals located at high altitudes see a high proportion of hypoxic children with bronchiolitis.…”
mentioning
confidence: 99%
“…13,100 Oxygen saturation changes as small as 2% significantly increase a physician' s decision for admission, and the diagnosis of hypoxemia by continuous pulse oximetry prolongs hospitalization, but there is no evidence that supplemental oxygen for transient desaturations benefits children. [101][102][103] Medium-chain acyl-coenzyme A dehydrogenase deficiency A portion of newborns identified by newborn screening may never experience symptoms of their enzymatic defect. Studies have identified affected but completely asymptomatic older siblings of screening-identified newborns, 11 and some mutations identified by newborn screening have acylcarnitine profiles that normalize over time.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%